PENGARUH PEMBERIAN JUS BUAH JAMBU BIJI (PSIDIUM GUAJAVA L) TERHADAP KELELAHAN OTOT ANAEROB DAN KADAR GLUKOSA DARAH PADA ATLET SEPAKBOLA REMAJA DI SALATIGA TRAINING CENTER (STC) - Rudy Widyasulistya; Ana Yuliah Rahmawati; Kun Aristiati Susiloretni (JURNAL RISET GIZI, 2018)
Background  : One athlete's performance is influenced by the availability of blood glucose during exercise. Carbohydrate drinks can supply energy during training and matches. Giving drinks containing 6-8% carbohydrates before exercise can help maintain blood glucose levels and delay fatigue in athletes. Objective  : To determine the effect of guava fruit juice on blood glucose levels and muscle fatigue on athletes as a result of the Training of Salatiga Training Center (STC). Method  : This type of research is Design Experiment with pre-post test control group design. The number of subjects was 26 soccer athletes aged 15-17 years at the Training Center for Salatiga Training Center (STC) who participated in the study. Research subjects received an intervention giving 250 ml of red guava juice and water drink (control). Drinks are given 30 minutes mid-workout. Muscle fatigue using the Running Anaerobic Sprint Test (RAST) method. Blood glucose levels and muscle fatigue are measured before and after exercise. Data were analyzed by paired t-test.Results  : The average initial blood glucose level of the treatment group was 116.84 mg / dl and the control group was 122.34 mg / dl. The average blood glucose level at the end of the treatment group was 111.46 mg / dl and the control group 99.53 mg / dl. The decrease in blood glucose levels was greater in the control group by 22.84 mg / dl while the treatment group was only 5.38 mg / dl. The average initial muscle fatigue of the treatment group was 2.57 watts / sec and the control group was 2.46 watts / sec. The average end muscle fatigue in the treatment group was 2.13 watts / sec and the control group was 2.75 watts / sec. Increased muscle loss was higher in the control group.Conclusion  : Giving red guava juice to athletes during the match can reduce the decrease in blood glucose levels during exercise compared to the control group (p = 0.012). There was no difference in giving guava juice to muscle fatigue in the youth soccer athletes of Diklat Salatiga Training Center (STC) (p = 0.26).